Automatic Face Recognition Using Facial Attractiveness การรู้จำหน้าคนแบบอัตโนมัติโดยใช้ความมีเสน่ห์ของใบหน้า - Kanghae, Sunthorn; Sornil, Ohm (NIDA Development Journal, 2012)
In this paper, we propose a system for automatic face recognition using a novel set of face features derived from facial attractiveness. The motivations for this technique come from psychological studies about the effects of facial attractiveness on human face recognition abilities and the ability of the Golden Mask to define ideal faces. A set of features is calculated from critical points on the face archetype and their corresponding points on the actual face. A neural network model is then used to identify an individual. Experimental evaluations using face images of 70 persons, with certain variations in light, background, image size, and facial expressions result in a recognition rate of 92.86%. บทความนี้นำเสนอระบบรู้จำหน้าคนแบบอัตโนมัติโดยใช้คุณลักษณะรูปแบบใหม่ที่สกัดจากความมีเสน่ห์ของใบหน้า วิธีการนี้ได้แรงบันดาลใจมาจากการศึกษาทางจิตวิทยาเกี่ยวกับอิทธิพลของความมีเสน่ห์ของใบหน้าต่อความสามารถในการจดจำหน้าของคนและความสามารถของหน้ากาก Golden Mask ในการปรับรูปใบหน้าให้มีความงดงาม ชุดของคุณลักษณะดังกล่าวจะคำนวณจากตำแหน่งอ้างอิงบนใบหน้าจริงและบนใบหน้าที่ได้รับการปรับให้มีเสน่ห์ในอุดมคติ และเครือข่ายประสาทเทียมถูกใช้เป็นตัวแบบในการระบุตัวบุคคล จากการทดลองกับรูปหน้าของกลุ่มตัวอย่างจำนวน 70 คน ซึ่งมีความแปรปรวนของ แสง พื้นหลัง ขนาดของภาพ และอารมณ์ของใบหน้า พบว่าวิธีการที่นำเสนอมีความถูกต้องของการรู้จำถึง 92.86 เปอร์เซ็น